Union Concessions following Asset Sales and Takeovers. (5th October 2018) - Lie, Erik; Que, Tingting
Abstract : We document that the likelihood of asset sales increases with union presence and union wages. Furthermore, acquiring firms gain significant concessions from the incumbent union following asset sales. Finally, the anticipation of union concessions helps explain the excess stock returns around asset sale announcements. We find no comparable effects for takeovers. We conclude that asset sales, but not takeovers, are partially motivated by the potential to extract concessions from unions.